2015
DOI: 10.1007/12_2015_324
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles of Conjugated Molecules and Polymers for Biomedical Applications

Abstract: Semiconducting organic materials based on π-conjugated molecules or polymers have recently received considerable attention for their use as imaging and therapeutic agents for biomedical applications. Because π-conjugated materials exhibit desirable characteristics such as high brightness, photostability, emission tunability, and low toxicity, they are an attractive alternative to conventional fluorophores. In this review, the recent development of π-conjugated molecular nanoparticles for in vitro and in vivo b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 159 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…Aqueous dispersions of NPs based on the push–pull molecules were obtained by the reprecipitation technique without addition of any surfactants or amphiphilic polymers. The technique is based on the formation of NPs due to a rapid change in the solvent polarity, which favors π–π packing and hydrophobic interactions. The size distribution of the NPs was assessed using the dynamic light scattering (DLS) method (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aqueous dispersions of NPs based on the push–pull molecules were obtained by the reprecipitation technique without addition of any surfactants or amphiphilic polymers. The technique is based on the formation of NPs due to a rapid change in the solvent polarity, which favors π–π packing and hydrophobic interactions. The size distribution of the NPs was assessed using the dynamic light scattering (DLS) method (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Under this background, the aqueous dispersions of OSC nanoparticles (NPs) as a facile strategy have been developed in recent years and some detailed reviews on the general preparation methods of OSC NPs were reported. 7,8 The hydrophobic organic π-conjugated small molecules or polymers can form stable nanocolloids when their solutions are dispersed in aqueous media. Apart from easy preparation and separation features, other advantages of NPs include high brightness, excellent photostability, low cytotoxicity, and high photoluminescence (PL) quantum yield (QY).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation